Sudden Stops and the Mexican Wave: Currency Crises, Capital Flow Reversals and Output Loss in Emerging Markets - Michael M. Hutchison; Ilan Noy (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
Sudden Stops are the simultaneous occurence of a currency/balance of payments crisis with a reversal in capital flows (Calvo, 1998). We investigate the output effects of financial crises in emerging markets, focusing on whether sudden-stop crises are a unique phenomenon and whether they entail an especially large and abrupt pattern of output collapse (a Mexican wave). Despite an emerging theoretical literature on Sudden Stops, empirical work to date has not precisely identified their occurences nor measured their subsequent output effects in broad samples. Analysis of Sudden Stops may provide the key to understanding why some currency/balance of payments crises entail very large output losses, while others are frequently followed by expansions. Using a panel data set over the 1975-97 period and covering 24 emerging-market economies, we distinguish between the output effects of currency crises, capital inflow reversals, and sudden-stop crises. We find that sudden-stop crises have a large negative, but short-lived, impact on output growth over and above that found with currency crises. A currency crisis typically reduces output by about 2-3 percent, while a Sudden Stop reduces output by and additional 6-8 percent in the year of the crisis. The cumulative output los of a Sudden Stop is even larger, around 13-15 percent over a three-year period. Out model estimates correspond closely to the output dynamics of the Mexican wave (such as seen in Mexico in 1995, Turkey in 1994 and elsewhere), and out-of-sample predictions of the model explain the sudden (and seemingly unexpected) collapse in output associated with the 1997-98 Asian Crisis. The empirical results are robust to alternative model specifications, lag structures and using estimation procedures (IV and GMM) that correct for bias associated with simultaneity and estimation of dynamic panel models with country-specific effect.
Keywords: 330; Währungskrise; Gesamtwirtschaftliche Produktion; Aufstrebende Märkte; Schwellenländer; Finanzkrise